Evaluación del efecto del rofecoxib en los cambios dentino-pulpares, el movimiento dental y la inhibición de la reabsorción radicular durante la aplicación de fuerzas ortodóncicas intrusivas (2005)
ABSTRACT: Root resorption associated to dental movement is an undesired side effect during orthodontic therapy. The purpose of this study was to identify the changes in the pulp-dentine organ, the degree of external root resorption, and the amount of dental movement in patients under Rofecoxib treatment, during the application of 2 ounce-intrusive orthodontic forces. The sample consisted of 6 subjects (12 teeth) on whom 8 teeth were evaluated as the experimental group (Rofecoxib) and 4 teeth as the control group (placebo). A fixed device (transpalatal bar) was used and a bracket was attached to the middle third of the buccal surface of the first upper premolar. On each segment a TMA wire with intrusive bends was set and activated every 6 weeks. The protocol of drug and placebo intake was determined by taking into account the stabilization of their concentration after regular administration. As part of the treatment, the premolars were extracted and prepared for histological examination. These cuts were dyed with Hematoxilin-Eosin colorants and Masson’s Trichoromic in order to observe them under the light microscope. The histological cuts showed more morphological changes at the odontoblastic layer, with increase in the number of collagen fibers and angiogenesis for the experimental group. In contrast, the control group presented more root damage than the experimental group. The range of dental movement under Rofecoxib was greater than the range under placebo after measuring the degree of dental movement. The rofecoxib showed to be effective in the inhibition of the RRE, compared with a medication placebo in this sample. With the current limitations to the rofecoxib use, one can say that the preferential inhibitors of the COX-2 present a better control that the specific inhibitors of the COX-2 in the dentinopulpar deleterious changes that are presented after the intrusive movement.